Case Report: The First Reported Concurrence of Wilson Disease and Bilateral Retinitis Pigmentosa - Ye, Zifan; Jia, Xiuhua; Liu, Xin; Zhang, Qi; Wang, Kaijun; Chen, Min (Frontiers in Medicine, 2022)
Background: Wilson disease (WD) and retinitis pigmentosa (RP) are common genetic disorders in clinical practice, however, the concurrence of WD and RP has never been reported before. WD occurs due to mutations that cause copper metabolic abnormalities; in turn, change in copper metabolism has been suggested to be related with RP. Here, we report the first case of concurrent WD and bilateral RP, and investigate possible pathogenesis to illuminate whether the two genetic disorders are causality or coincidence. Case Presentation: The patient was a 43-year-old Chinese female diagnosed with WD 12 years ago. She had suffered from night blindness since childhood and faced diminution of bilateral vision within 10 years, for which she was referred to our Eye Center during hospitalization for routine copper excretion treatment. The ceruloplasmin, skull magnetic resonance imaging (MRI), and abdominal ultrasound results accorded with hepatolenticular degeneration. Ocular examinations revealed corneal Kayser-Fleischer (K-F) ring, sunflower-like cataract, retinal osteocyte-like pigmentation, bilateral atrophy of outer retina, cystoid macular edema (CME), and tubular vision in both eyes. Phacoemulsification combined with intraocular lens implantation was performed in the right and left eye, but there was limited improvement in her visual acuity. Whole exome sequencing (WES) detected a deleterious homozygous mutation in the ATP7B gene related to WD, and a homozygous mutation in the CNGA1 gene very likely to cause RP. Conclusions: We reported the first case of concurrent WD and RP. WES detected two pathogenic gene mutations, ATP7B and CNGA1. Though we cannot completely rule out a causal effect of WD-related abnormal copper metabolism with RP, we speculate that the two gene mutations lead to the coincidence of the two genetic disorders respectively.